2021
DOI: 10.3390/nano11102731
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic, Phonon and Optical Properties of Pure and Ion-Doped YFeO3 Nanoparticles

Abstract: The magnetic, electric, phonon and optical properties of pure and ion-doped orthorhombic YFeO3 nanoparticles are studied for the first time theoretically. The spontaneous magnetization Ms in YFeO3 decreases with decreasing particle size. Ms is also shape dependent. The magnetization increases by Co and Er ion doping and decreases by Ti doping, which is caused by the different strain which appears in the nanoparticles and changes the exchange interaction constants in the doped states. The phonon energy for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…9,10 To improve the magnetic behavior and optical properties of YFO, the researchers/scientists were tried to create the distorted orthorhombic structure via doping of different ionic radii atoms at either Y site or Fe site. [11][12][13][14][15] As a result of distorted crystal structure, the enhanced magnetization values were observed and reported in the literature. [11][12][13][14][15] In this regard Bhardwaj et al, prepared the distorted orthorhombic crystal structure of YFO by doping of Sm (15 mol%) and Nd (15 mol%).…”
mentioning
confidence: 59%
“…9,10 To improve the magnetic behavior and optical properties of YFO, the researchers/scientists were tried to create the distorted orthorhombic structure via doping of different ionic radii atoms at either Y site or Fe site. [11][12][13][14][15] As a result of distorted crystal structure, the enhanced magnetization values were observed and reported in the literature. [11][12][13][14][15] In this regard Bhardwaj et al, prepared the distorted orthorhombic crystal structure of YFO by doping of Sm (15 mol%) and Nd (15 mol%).…”
mentioning
confidence: 59%
“…The tensile strain in the case of Sm‐ or Gd‐doped LuFO could be compared with ion‐doped YFeO 3 $_{3}$ (YFO) where the ionic radius of Y (1.04 Å) is nearly the same as that of Lu and thus smaller than the radius of the Sm or Gd doping ions. Recently, Apostolov et al [ 31 ] showed that P s $P_{\text{s}}$ decreases with increasing Sm concentration in YFO. It must be noted that with our model we can explain also the decrease of P s $P_{\text{s}}$ in La‐doped LuFO observed recently by Leelashree et al [ 16 ] where a tensile strain appears, because the ionic radius of the doping La ion is larger than that of the host Lu ion.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Theoretical investigations have delved into the differences in multiferroic properties between hexagonal and orthorhombic ion-doped YFO nanoparticles. [23] Earlier research reports have highlighted the alterable structural and physical characteristics of YFO through changes in particle size, chelating agent, or adding magnetic or nonmagnetic ions at A-sites or B-sites. [15,16,18,[23][24][25][26][27] For instance, the altered magnetic properties of single phase of Y 1Àx Sc x FeO 3 (x = 0, 0.5, and 1) and Y 1Àx A x B y Fe 1Ày O 3 (where A = Gd 3þ , Nd 3þ , Sm 3þ and B = Ti 4þ ) nanoparticles have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Earlier research reports have highlighted the alterable structural and physical characteristics of YFO through changes in particle size, chelating agent, or adding magnetic or nonmagnetic ions at A-sites or B-sites. [15,16,18,[23][24][25][26][27] For instance, the altered magnetic properties of single phase of Y 1Àx Sc x FeO 3 (x = 0, 0.5, and 1) and Y 1Àx A x B y Fe 1Ày O 3 (where A = Gd 3þ , Nd 3þ , Sm 3þ and B = Ti 4þ ) nanoparticles have been observed. [15,16,27] Apart from these, improved magnetic properties of YFO nanomaterial obtained from tartaric acid (as a chelating agent) compared to YFO nanomaterial obtained from citric acid, oxalic acid, and sucrose have been reported.…”
Section: Introductionmentioning
confidence: 99%